Molecular identification of actinomycetes with antimicrobial, antioxidant and anticancer properties - Abdel-Aziz, Mohamed S; Hathout, Amal S; El-Neleety, Aziza A; Hamed, Ahmed A; Sabry, Bassem A; Aly, Soher E; Abdel-Wahhab, Mosaad A (Comunicata Scientiae, 2019)
The objectives of this study were to isolate and identify the actinomycetes strains from the soil and marine sediments and to evaluate the antimicrobial, antioxidant and cytotoxic activity of their bioactive secondary metabolites. Eight actinomycetes strains were isolated from soil and marine sediment samples collected from different areas in Egypt. Only three actinomycetes exhibited a wide spectrum of antimicrobial activities. They were active in vitro against microbial pathogen viz: Staphylococcus aureus, Escherichia coli, Salmonella typhi, Aspergillus parasiticus, Fusarium solani and Fusarium oxysporum. These promising isolates were selected and identified using molecular identification technique and identified as Streptomyces spp. The crude extracts from the three Streptomyces exhibited potent antimicrobial activities against a set of microbial pathogens as well as antioxidant and anticancer activity in human hepatocellular carcinoma cell line (HepG2). The crude extract of Streptomyces isolate D showed antitumor activity with lC50 0.85 µg/ mL. Forty compounds were identified from the two most promising ethyl acetate extracts of culture broth of Streptomyces sp. (D-EGY) by Gas Chromatography-Mass Spectrometry analysis. It could be concluded that the streptomycetes isolated from the Egyptian environment are promising candidates as antimicrobial, antioxidant and anticancer.